A Rare Case of Childhood Hypertension and Hyponatremia - Mazumdar, Jayitri; Sarkar, Rakesh; Pal, Sumita; Ghiosh, Sukumar; Das, Pradip Kumar (Journal of Pediatric Nephrology, 2015)
Hypertension and hyponatremia together, is an uncommon entity in children. We here described a 10-year-old boy presented with hypertensive emergency and altered sensorium with hyponatremia. After initial stabilization USG (ultrasonography) Doppler showed shrunken right kidney with absence of flow in the right renal artery. Right Renal Resistive Index was 0.9. Therefore, patient underwent right total nephrectomy and blood pressure ultimately came under control. Keywords: Hypertension; Hyponatremia; Child.